Capacity Optimization for Electrical and Thermal Energy Storage in Multi-energy Building Energy System. (February 2019) - Zhu, Qianwen; Li, Qiqiang; Zhang, Bingying; Wang, Luhao; Li, Guanguan; Wang, Rui
Abstract: In a multi-energy building energy system, the key to improve the energy efficiency and economy is coordinating the capacity configuration and operation scheduling of both electrical and thermal energy storage. Considering the electricity storage characteristics of electricity feedback arbitrage and degradation, as well as part load rate and ON/OFF time constraints for the combined operation of thermal energy storage and ground source heat pump, this paper presents a bi-level optimization method, including upper capacity optimization and lower operation optimization. The simulation results show that, compared to the system without energy storage, the proposed method significantly reduces total annualized cost, shifts large amounts of peak load and increases renewable energy self-consumption rate.